Multimodal Risk-Adapted Treatment in Surgical Patients With Synovial Sarcoma: A Preoperative Nomogram-Guided Adjuvant Treatment Strategy - Zeng, Ziliang; Yao, Hao; Lv, Dongming; Jin, Qinglin; Bian, Yiying; Zou, Yutong; Tu, Jian; Wang, Bo; Wen, Lili; Xie, Xianbiao (Frontiers in Surgery, 2020)
Background Synovial sarcoma is characterized by heterogeneous clinical manifestations, making it difficult to evaluate individual patients’ prognoses and design personal treatment schemes. We established an effective preoperative nomogram to predict cancer-specific survival (CSS) and present a risk-adapted adjuvant treatment strategy in surgical patients with synovial sarcoma. Methods This retrospective study included patients from the Surveillance, Epidemiology, and End Results (SEER) database who were diagnosed with synovial sarcoma between 1996 and 2015. The patients were randomly divided into training and validation groups. The predictors were selected using univariate and multivariate Cox hazards models. The nomogram performance was verified for its discriminatory ability and calibration. We further stratified the patients into different risk groups according to the nomogram scores and compared the efficacy of chemotherapy, radiotherapy and combination of radiotherapy and chemotherapy. Results There were 915 patients enrolled in our study, with 874 patients either alive or dead due to synovial sarcoma. We established a nomogram to predict 5-year CSS based on independent factors, including sex, age, grade, tumor size, location and extend (all p<0.05). Our model showed a consistently good discriminatory ability and calibration for predicting 5-year CSS in both the training (c-index = 0.78, 95% CI 0.75-0.81) and validation (c-index = 0.73, 95% CI 0.68-0.78). Based on their nomogram scores, we divided patients into 5 groups. Compared to patients without adjuvant treatment, nomogram I patients with adjuvant treatment had no improvements in 5-year CSS (100.0% vs. 100.0%), nomogram II patients had higher 5-year CSS with radiotherapy or chemotherapy (92.9% vs. 72.2%, p=0.015), nomogram III patients had higher 5-year CSS with combination of chemotherapy and radiotherapy (70.1% vs. 47.2%, p=0.004), nomogram IV patients had higher 5-year CSS with radiotherapy (41.3% vs. 15.6%, p=0.015), and nomogram V patients had no improvements in 5-year CSS rates with adjuvant treatment (28.9% vs. 16.9%, p=0.18). Conclusion The nomogram showed a satisfactory discriminatory ability and calibration for predicting 5-year CSS in synovial sarcoma patients. Based on this nomogram, we stratified synovial sarcoma patients according to risk levels, which enabled us to provide a useful grouping scheme that can inform multimodal risk-adapted treatment in synovial sarcoma.